The complex relationship between interrogation techniques, suspects changing their statement and legal assistance: evidence from a Dutch sample of police interviews - Verhoeven, Willem-Jan (Policing and society, 2018)
This study aims to provide more insight in the complex and dynamic relationships between interrogation techniques, changes in suspects’ statements and the presence of a lawyer. In doing so, it shows the importance of taking into account the conditions under which interrogation techniques can elicit statements from suspects. Based on a Dutch sample of 168 police interviews of suspects in homicide cases structural equation modelling is used to analyse (1) the extent to which interrogation techniques mediate suspects changing their statement and (2) the extent to which the presence of a lawyer moderates the relationship between interrogation techniques and suspects changing their statement. The results show that manipulative interrogation techniques mediate the changing statement of silent suspects compared to suspects who give a statement on personal matters or deny only during interviews without a lawyer. Based on the findings it can be concluded that the presence of a lawyer can change the dynamics of police interviews of suspects. This is an important conclusion given the European developments in strengthening the safeguards of the rights of suspects in police custody. The presence of a lawyer might contribute to reducing false confessions, avoid tunnel vision, and prevent miscarriages of justice.